Assessing tuna populations around fads in Tabam waters for coastal management - Mutmainnah Ridwan; Alfi Umahuk; Martini Djamhur; Yuliana Recar; Saptariani Putri Ridwan; Edy Miswar; Edwarsyah Edwarsyah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Tabam waters are waters in Ternate City where the average population works as fishermen using gillnet fishing gear with the target fish being tuna (Eutynnus affinis) locally called Tongkol. Fishing activities in this area are generally carried out around FADs. Fishing that is carried out on an increasing basis and accompanied by an increase in gillnet fishing gear can endanger the sustainability of mackarel tuna/ tuna fish/komo tuna. Therefore, to maintain the sustainability of tuna fish resources in Tabam waters, an assessment of the biological status is needed which includes the structure of length, weight, circumference, growth patterns, and age groups. Establish guidelines for fishermen on the appropriate size of tuna to be harvested in order to preserve the sustainability of the tuna population. This research was conducted in December 2018-March 2019, using a sample size of 200 fish, using a survey method. The survey was conducted by examining the technical characteristics of gillnet fishing gear, FAD aids, and tuna catches. The results showed that the average fish caught was gilled with an isometric growth form and the average age group of tuna fish was around 21.7 cm, 17.2 cm, 18.9 cm, and 21.0 cm.Keywords:GillnetFADSAsessingKomoTunaTabam